Formation of compact systems of super-Earths via dynamical instabilities and giant impacts. Issue 4 (28th November 2019) - Poon, Sanson T S; Nelson, Richard P; Jacobson, Seth A; Morbidelli, Alessandro
ABSTRACT: The NASA's Kepler mission discovered ∼700 planets in multiplanet systems containing three or more transiting bodies, many of which are super-Earths and mini-Neptunes in compact configurations. Using N -body simulations, we examine the in situ, final stage assembly of multiplanet systems via the collisional accretion of protoplanets. Our initial conditions are constructed using a subset of the Kepler five-planet systems as templates. Two different prescriptions for treating planetary collisions are adopted. The simulations address numerous questions: Do the results depend on the accretion prescription?; do the resulting systems resemble the Kepler systems, and do they reproduce the observed distribution of planetary multiplicities when synthetically observed?; do collisions lead to significant modification of protoplanet compositions, or to stripping of gaseous envelopes?; do the eccentricity distributions agree with those inferred for the Kepler planets? We find that the accretion prescription is unimportant in determining the outcomes. The final planetary systems look broadly similar to the Kepler templates adopted, but the observed distributions of planetary multiplicities or eccentricities are not reproduced, because scattering does not excite the systems sufficiently. In addition, we find that ∼1 per cent of our final systems contain a co-orbital planet pair in horseshoe or tadpole orbits. Post-processing the collision outcomes suggests that they would not significantly change the ice fractions of initially ice-rich protoplanets, but significant stripping of gaseous envelopes appears likely. Hence, it may be difficult to reconcile the observation that many low-mass Kepler planets have H/He envelopes with an in situ formation scenario that involves giant impacts after dispersal of the gas disc.